(3GdcTa hGdHjGfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI Bd YeQGf Hbhdg (B: (3ShQI Bd YeQGf eOjfI KeGfhf cdeI heG jJi BjI s
(3BNQgG (B:s
(3BNQ ShQI Bd YeQGf (B: (3aGJbhG Gdg GdCQV hGdSeGA dYdce JadMhf ai OGQ GdHbGA Je GdLRA s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3JaSjQ (B100) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs